Metabolome-wide Mendelian randomisation reveals causal links between circulating metabolites and type 1 diabetesResearch in context - Basile Jumentier; Isabel Gamache; Dominika A. Michalek; Wei-Min Chen; Suna Onengut-Gumuscu; Stephen S. Rich; Constantin Polychronakos; Despoina Manousaki (EBioMedicine)
Summary: Background: Type 1 diabetes (T1D) is an autoimmune disease that causes destruction of the insulin-producing pancreatic beta cell, resulting in high levels of blood glucose and profound alterations in carbohydrate, lipid, and protein metabolism if untreated. We aimed to identify if circulating metabolites are causally linked to risk of T1D, using two-sample Mendelian Randomisation (MR). Methods: For our discovery and replication MR analyses, we used SNP-instruments for circulating metabolites measured in seven large GWAS in Europeans. The corresponding effects of the SNP-instruments on T1D were derived from GWAS in multiple ancestries. The MR effects were estimated using the Wald Ratio or the Inverse Weighted Variance method. We then tested the presence of shared causal variants between the candidate metabolites and T1D and performed sensitivity analyses for pleiotropy and direction of causality. Findings: Of the 1679 tested metabolite-T1D associations, 46 metabolites showed effects on T1D accounting for multiple testing. Among the 14 metabolites replicated using independent T1D GWAS, 7 of these metabolites shared a causal variant with T1D. The metabolite with the most important MR effect, vanillactate, showed a strong negative association with T1D risk in 3 T1D GWAS. The SNP-instrument of vanillactate is an eQTL of the TH gene which is itself coexpressed with the INS gene, a major T1D locus. Interpretation: Combining evidence from MR and various follow-up analyses, we identified causal circulating metabolites for T1D, highlighting the role of specific metabolic signatures in the pathogenesis of this disease. Funding: Fonds de Recherche du Quebec-Santé (FRQS).